2008
DOI: 10.1007/s10008-008-0615-2
|View full text |Cite
|
Sign up to set email alerts
|

Ferricyanide immobilized within organically modified MCM-41; application for electrocatalytic reduction of hydrogen peroxide

Abstract: Carbon paste electrode modified with aminated Mobil Catalytic Material Number 41 (MCM-41) was prepared and used for immobilization of K 3 [Fe(CN) 6 ] in acidic medium, and then electrochemical behavior of modified electrode containing ferricyanide was studied in detail, including pH-dependence and scan rate effect. Cyclic voltammetry studies showed that the electrode reaction is a surface-controlled process at the scan rate range from 5 to 60 mV s −1 . Also, the electrocatalytic behavior of modified electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, Xia et al and Yang et al reported that Fe(CN) 6 3− was unstable in acidic conditions [34,35]. Thus, the acid pretreatment experiment for the MCF-IL-Fe(CN) [20]. By comparing the differences in cyclic voltametric responses of H 2 O 2 on the freshly prepared MCF-IL-Fe(CN) 6 3− /PVA electrode and the acid-pretreated one, it can be seen that the acid treatment greatly affected the characteristics of the electrode.…”
Section: Electrochemical Characterizations Of Mcf-il-fe(cn)6 3− /Pva ...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, Xia et al and Yang et al reported that Fe(CN) 6 3− was unstable in acidic conditions [34,35]. Thus, the acid pretreatment experiment for the MCF-IL-Fe(CN) [20]. By comparing the differences in cyclic voltametric responses of H 2 O 2 on the freshly prepared MCF-IL-Fe(CN) 6 3− /PVA electrode and the acid-pretreated one, it can be seen that the acid treatment greatly affected the characteristics of the electrode.…”
Section: Electrochemical Characterizations Of Mcf-il-fe(cn)6 3− /Pva ...mentioning
confidence: 99%
“…Imidazolium-based ILs are one of the most popular ionic liquids because of their inherent properties and tunable nature. Compared with the commonly used groups (-NH 2 , -R-NH 4 + ) for Fe(CN) 6 3− confinement [14,20,21], imidazolium-based ILs have recently attracted considerable attention because the strong interaction between the imidazolium moieties and Fe(CN) 6…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apply modified-MCM-48 as catalyst has advantages like high stability under severe condition such as high temperature and organic solvent and easy separation process [1][2][3][4][5][6]. The surfaces of the MCM-48 have a large number of silanol groups that reaction with various alkoxysilanes by covalent grafting for manufacture functionalized MCM-48 [7]. Schiff bases are condensation products of primary amines and carbonyl compounds (also known as imine or azomethine).…”
Section: Introductionmentioning
confidence: 99%